The political career of W. Kerr Scott : the squire from Haw River - Pleasants, Julian M. (New directions in southern history., 2014)
The political biography of Kerr Scott covers his career in North Carolina as commissioner of agriculture (1936-1948), governor (1949-1953) and US senator (1954-1958). His progressive reforms, which changed the course of North Carolina's history, made him one of the most influential governors in the state's history. In 1954 he was elected to the US Senate, where he served effectively until his death in 1958.